2017
DOI: 10.1038/s41598-017-03044-w
|View full text |Cite
|
Sign up to set email alerts
|

Soil biochemical responses to nitrogen addition in a secondary evergreen broad-leaved forest ecosystem

Abstract: In order to investigate the effects of N deposition on soil biochemistry in secondary forests, one N addition experiment was conducted in a secondary evergreen broad-leaved forest in the western edge of Sichuan Basin, with the highest level of background N deposition (about 95 kg N ha−1 yr−1) in China. Three N treatment levels (+0, +50, +150 kg N ha−1 yr−1) were monthly added to soil surface in this forest beginning in April 2013. Soil biochemistry and root biomass of the 0–10 cm soil horizon were measured fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 66 publications
3
18
0
Order By: Relevance
“…In this study, after two years of simulated N deposition, the MBC and MBN values in the L, M, and H treatments were significantly lower than those in the Ctr treatment ( Fig 6A and 6B ). Simulated N deposition significantly decreased MBC and MBN in our study, and this result is in line with previous studies in other forest ecosystems [ 9 , 22 , 26 , 27 , 65 ]. Furthermore, we also found that N deposition significantly decreased the concentration of DOC ( Fig 6C ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, after two years of simulated N deposition, the MBC and MBN values in the L, M, and H treatments were significantly lower than those in the Ctr treatment ( Fig 6A and 6B ). Simulated N deposition significantly decreased MBC and MBN in our study, and this result is in line with previous studies in other forest ecosystems [ 9 , 22 , 26 , 27 , 65 ]. Furthermore, we also found that N deposition significantly decreased the concentration of DOC ( Fig 6C ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies found that fine root biomass is significantly and positively correlated with soil respiration [ 52 , 59 , 60 ]. Similar to the results of this study, many previous studies found that N deposition can decrease root biomass, which leads to less input from belowground roots to the soil [ 22 , 27 , 28 , 61 ]. In our study, we found that fine root biomass was significantly reduced by simulated N deposition ( P < 0.05, Fig 6E ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All these mentioned reasons explain why we found no or only minor changes of the soil microbial communities to the moderate long-term N addition at this forest site. The bacterial and fungal abundance remained unchanged, which is in agreement with others (Peng et al, 2017;Forstner et al, 2019b). Similarly, Hesse et al (2015) found no change in fungal biomass in a natural maple forest in USA treated with N for 16 years.…”
Section: Long-term N Addition Effects On Soil Microbial Communitiessupporting
confidence: 88%